Building financial resilience through financial and digital literacy in South Asia and Sub-Saharan Africa - Angela C. Lyons; Josephine Kass-Hanna; Fan Liu; Andrew J. Greenlee; Lianyun Zeng (Asian Development Bank Institute (ADBI), 2020)
Globally, 1.7 billion adults still lack access to formal financial services, with a large percentage living in South Asia and Sub-Saharan Africa. Current financial inclusion strategies provide these vulnerable populations with access to a wide array of financial services that aim to build more inclusive and financially resilient societies. With the movement towards Fintech and over 67% of the world's population having a mobile phone, digital financial literacy is gaining momentum. Nevertheless, negligible research has measured its impacts on financial behavior. This study uses data from the InterMedia Financial Inclusion Insights surveys for seven South Asian and Sub-Saharan African countries to investigate the impact of multi-dimensional measures of financial and digital literacy on resilience-building financial behaviors, including saving, borrowing, and risk management. The findings consistently show that both financial and digital literacy are key factors to building inclusiveness and financial resilience. Heterogeneities are identified across regions, as well as for poor, rural, and female households. A robustness check is also included to address potential endogeneity. The results emphasize the need to redefine traditional financial literacy to include digital literacy, with important implications for countries considering both financial and digital literacy as a dual approach to improving households' long-run financial resilience.
Keywords: D14; D31; D91; G21; G23; J11; O17; O53; 330; financial resilience; financial behaviors; financial literacy; digital literacy; South Asia; Sub-Saharan Africa